Politics as symbolic action mass arousal and quiescence - Edelman, Murray J. (Murray Jacob), 1919-2001 (Institute for Research on Poverty. Monograph series, 1971)
Politics as Symbolic Action: Mass Arousal and Quiescence deals with the dynamics of development of political threats related to political behavior. The book discusses the conditions under which the dynamics related to political behavior are the prior causes of political arousal, violence, and quiescence.